Organization of Inclusive Teaching for Children with sud at the Good Start Children’s Center in Limete in Kinshasa. Look and Perspectives (Global Journal of Human-Social Science, 2023)
Children with trisomy 21 commonly referred to as Down syndrome or Down syndrome in the Anglo-Saxon space with an average intelligence quotient of 50 are unable to pursue an ordinary pace of learning in various fields such as mathematics reading writing because of their slower rhythms The presence of one more chromosome in their body 47 chromosomes instead of 46 makes these children unable to meet the requirements and rigors of ordinary schools In view of their lower intellectual level they deserve individualized teaching adapted to the pace and needs of the child To allow educators to easily follow up the number of children must be reduced in the room with an average of 7 students in a classroom The scientists who are in the laboratories of the educational apparatus propose suitable solutions for the integration of these children into society according to their needs and rhythms to reinvigorate and balance the demands of inclusive education
Keywords: organization; inclusive teaching; child with down syndrome